Emerging concepts in heart failure management and treatment: focus on current guideline-directed medical therapy for heart failure with reduced ejection fraction - Oscar Eduardo Ospina González; Diana Catalina Llanos Mejía; Edgardo Kaplinsky; Alejandro Barbagelata; Sergio Perrone (BioExcel Publishing Ltd, 2023)
One of the most relevant and differentiating aspects provided by the 2021 European Society of Cardiology guidelines for the diagnosis and treatment of acute and chronic heart failure is the retraction of the historical stepped and vertical pharmacological treatment scheme for heart failure with reduced ejection fraction (HFrEF). Subsequently, it was replaced by an updated algorithm that places four therapeutic families in the same initial horizontal step with an equally high degree of recommendation (class I). In this context, these four pillars, which have demonstrated a significant reduction in mortality and hospitalizations in patients with HFrEF, include (1) angiotensin-converting enzyme inhibitors (ACEi)/angiotensin receptor blockers (ARB)/angiotensin II receptor-neprilysin inhibitors (ARNi), (2) beta blockers, (3) mineralocorticoid receptor antagonists (MRA) and (4) sodium-glucose cotransporter 2 inhibitors (SGLT2is) as the main novelty. This manuscript reviews the current therapeutic algorithm with a special focus on the therapeutic value of adding an MRA (still underused in both clinical trials and real world), changing an ACEi/ARB for an ARNi and incorporating an SGLT2i in patients with HFrEF. This article is part of the Emerging concepts in heart failure management and treatment Special Issue: https://www.drugsincontext.com/special_issues/emerging-concepts-in-heart-failure-management-and-treatment